Stamped from the beginning : the definitive history of racist ideas in America - Kendi, Ibram X. (Nation Books, 2016)
Americans like to insist that we are living in a postracial, color-blind society. In fact, racist thought is alive and well; it has simply become more sophisticated and more insidious. And as historian Ibram X. Kendi argues, racist ideas in this country have a long and lingering history, one in which nearly every great American thinker is complicit. Kendi chronicles the entire story of anti-Black racist ideas and their staggering power over the course of American history. Stamped from the Beginning uses the lives of five major American intellectuals to offer a window into the contentious debates between assimilationists and segregationists and between racists and antiracists. From Puritan minister Cotton Mather to Thomas Jefferson, from fiery abolitionist William Lloyd Garrison to brilliant scholar W.E.B. Du Bois to legendary anti-prison activist Angela Davis, Kendi shows how and why some of our leading proslavery and pro-civil rights thinkers have challenged or helped cement racist ideas in America. As Kendi provocatively illustrates, racist thinking did not arise from ignorance or hatred. Racist ideas were created and popularized in an effort to defend deeply entrenched discriminatory policies and to rationalize the nation's racial inequities in everything from wealth to health. While racist ideas are easily produced and easily consumed, they can also be discredited.